El discurso tecnocientífico en la construcción estética del cuerpo en la publicidad de cosméticos - Cely Álvarez, Adriana (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
The paper presents two theoretical categories that describe the relationship of body and technology recreated in advertising discourse. On one hand, it refers to the development of techno-scientific aesthetic of body expressed in the speech wordvisual of advertising and, secondly, the narrative on the development of a flexible body in response to the demands of modern biopolitical societies. We analyze an announcement concerning cosmetic products, to explore the discursive elements that build metonymy, metaphor, myth and chronotopes concerning science fiction. Finally, the image shows the body gives examined possible through the use of technoscientific discourse in which there are traces of the development of a strong and flexible body space.